Literary Activities of Students and Professors of Kražiai College in the Seventeenth Century: Works Dedicated to Jonas Karolis Chodkevičius - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2024)
The article continues the cycle of studies on the literary activities of the students and professors of Kražiai College in the seventeenth century. The first article of the cycle addressed the state of research into the activities and history of Kražiai College, the problems related to the classification of extant works, and included the analysis of the works dedicated to the bishops of Samogitia. The second article dealt with the works dedicated to the elders of Samogitia by presenting their structure, peculiarities, and genres, analysing the issues of authorship, and discussing their significance and place in the Latin literature of the Grand Duchy of Lithuania. The present article, the third in the series, discusses two works dedicated to Jonas Karolis Chodkevičius (Jan Karol Chodkiewicz, c.1570–1621), the founder of the college. These are Obsequium gratitudinis (Humble Gratitude) published in 1619 and Sacra lithothesis (Consecration of the Stone) published in 1621. Motiejus Kazimieras Sarbievijus (Mathias Casimirus Sarbievius, 1595–1640) is considered the author of both works. This introduction of the works includes a detailed outline of their structure and a discussion of their features. The reports (annuae litterae), historical sketches (historiae), and short catalogues (catalogi breves) of Kražiai College were used to add further data and details related to the origin of the appearance of these works.Obsequium gratitudinis is a seventeenth-century panegyric of the traditional structure (the coat of arms of the dedicatee with a coat-of-arms poem, a dedication in prose, epigrams, elogia, and a poem) glorifying the dedicatee in the way most popular at the time – by resorting to the symbolism of the figures (most frequently a Griffin) on his coat of arms. Yet the unevenness of the individual texts of the work catches the eye: conceptualism, ingenuity, and wit are characteristic of the epigrams, while pathos, pomposity and sophistication stand out in the poem. Some epigrams of the work (XII, for instance) illustrate the propositions of Sarbievius in his work De acuto et arguto (On Acute and Witty Style). It is also important that the erection of the monument, which is depicted in this early work in a somewhat pretentious yet ingenious manner would be described by Sarbievius in his theoretical works (Characteres lyrici, lib. I, character V, II) as one of the possible ways of writing odes and applied in the poet’s mature work on a number of occasions.Sacra lithothesis is dedicated to the ceremony of the laying of the foundation stone of the church of Kražiai College in 1621 and to its founder Chodkevičius. The composition and artistic execution of the work point to the changes in Sarbievius’s work. The first two parts are typical of most panegyric works: a coat of arms with a coat-of-arms poem and a prose dedication. The verses to the Griffin on Chodkevičius’s coat of arms could be seen as a separate part. What follows (and what is not to be found in any other seventeenth-century work created in Kražiai) are interestingly composed four main parts (an engraving with inscriptions, a poem, an epigram, an ode), which glorify Chodkevičius’s virtues (piety, generosity, fairness, and courage). However, the history of the work is not entirely clear and contradicts some of the propositions considered indisputable so far. The analysis of the material from the archives of the Society of Jesus in Rome shows that (1) the work had already been printed and handed out to the participants in the ceremony, which means that the exact time of its writing is uncertain; (2) Sacra lithothesis could not have been acted out during the ceremony of the laying of the foundation stone of the church of Kražiai College (which has been assumed up until now) as another work that was performed – actus de immunitate ecclesiastica – is explicitely mentioned, and (3) it is unlikely that Chodkevičius, the dedicatee of the work, was present at the ceremony as its detailed descriptions do not mention him. It is also obvious that he did not founder the construction of the church of Kražiai College: it remained a dear yet unfulfilled wish of the hetman.Obsequium gratitudinis and Sacra lithothesis had never been reprinted as complete works. The epigrams of the former (X, XI, I, IX) were included in the collections of Sarbievius’s works during his lifetime. In the eighteenth-century and later collections, Obsequium gratitudinis is ‘divided’ into separate segments. Sarbievius corrected and rewrote the odes of Sacra lithothesis. They were published in his collections of lyrical poetry: the first two in 1625, the fourth in 1628. Some of the texts of the work were included in Sarbievius’s poetry collections compiled in the eighteenth and nineteenth centuries.Both of Sarbievius’s works dedicated to Chodkevičius point to the successful beginning of his literary path. They are characterised by an inventive structure, composition, ambition, and a search for new forms and laudatory possibilities, which are also indicative of his theoretical work on poetics and rhetoric. Moreover, these works are harmoniously integrated into the whole of Latin panegyrics of the early seventeenth century in the Grand Duchy of Lithuania and are an important part of this heritage.
Keywords: Kražiai College; Jesuit students and professors; Samogitia; Jan Karol Chodkiewicz; Mathias Casimirus Sarbievius; Lithuanian literature (Latin); panegyric